Bridging Islamic and Conventional Finance through Integration of Knowledge (IoK): The Potential of the Third Sector - Omercic, Jasmin (International Journal of Islamic Economics and Finance (IJIEF), 2023)
Finance is integral to civilizational prosperity yet has impacted the global development of recent centuries, proved inherently inconsistent, and created multiple issues, i.e., inequalities. In this regard, Islamic finance (IF) offers solutions. Moreover, contemporary appraisals of the Integration of Knowledge (IoK) methodology represent a novel alternative to extant challenges and issues. The paper’s objectives are, therefore, to propose an IoK model of Islamic and conventional financial (CF) convergence with leverage to fintech and demonstrate the potential of the waqf sector for such convergence and its equivalent revival and reform along such methodological contours. This paper is a methodological contribution. However, library research, critical content analysis, and heterodox methods of concretization, synthesis, and transdisciplinary analytical reasoning substantiate the paper’s methodology. Islamic sources of knowledge, i.e., Qur’an, justify this study’s unorthodox methodology. A background depicts the CF problems and persistent issues that justify alternatives. It is followed by rationalizing IE development via IoK to converge IF and CF. The IoK model developed for IE development follows and is schematically demonstrated as novel findings of this paper to bridge the gap between IF and CF and leverage waqfs’ role and potential. Greater reference to waqf projects institutionalized implications for IF and integration with CF. Further, leveraging waqf and even fintech as an indicator of digitalization within the IoK model has implications for attaining the defined maqāṣid and developing IE genuinely. A conclusion summarizes and provides actionable recommendations linked with the IoK model’s objectives to reform extant IF and conventional practice based on sound Islamic philosophical foundations and maqāṣid-oriented envisioning of IE development.